2002
DOI: 10.1248/jhs.48.273
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Extracts Prepared from Tropical and Subtropical Plants on Methicillin-Resistant Staphylococcus aureus.

Abstract: The antibacterial activity of the extracts prepared from 181 species (75 families) of tropical and subtropical plants was screened against various types of pathogenic bacteria. Among the 505 extracts tested, 53 of them inhibited the growth of methicillin-resistant Staphylococcus aureus (MRSA). The active extracts obtained from barks of Shorea hemsleyana and roots of Cyphostemma bainessi were separated to their components, some of which greatly reduced the viable cell number of MRSA. These active compounds were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(77 citation statements)
references
References 9 publications
(11 reference statements)
2
74
0
Order By: Relevance
“…Several Achillea plants have been found to possess antiseptic and infection preventing properties [38,39]. They are being used as ingredients in medicinal and cosmetic preparations [40].…”
Section: Discussionmentioning
confidence: 99%
“…Several Achillea plants have been found to possess antiseptic and infection preventing properties [38,39]. They are being used as ingredients in medicinal and cosmetic preparations [40].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, analyses of growth inhibition activity performed by using the well diffusion method showed that all the tested plants, which are commonly used by traditional medical practitioners, exhibited moderate activity against clinical isolates of bacterial strains at extract concentrations of 1 mg/ml Nitta et al, 2002;Voravuthikunchai and Kitpipit, 2005). Infections caused by multiple drug resistance, including resistance to β-lactam, are among the most difficult infections to treat (Abu-Shanab et al, 2004, 2006Kim et al, 2005).…”
Section: Discussionmentioning
confidence: 64%
“…The MIC and MBC values obtained for the extracts against the bacterial strains support the findings obtained by using the well diffusion method. One concern is that, for the extracts obtained in this study, MIC values were lower than MBC values, thus suggesting that these extracts are bacteriostatic at lower concentrations and bactericidal at higher concentrations (Abu-Shanab et al, 2006;Nitta et al, 2002;Ross et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…The reason may be due to the extracts' hydrophobicity, which caused cell rupture as a result of the destruction of the membrane's structure (Nitta et al, 2002).…”
Section: Ajptmentioning
confidence: 99%